COOKBOOK Yellow cassava - Ospina Portilla, Maria Alejandra; Ramos Medina, Irma Paola; Trivino Palacios, William (2023)
Deficiencies of micronutrients, such as vitamin A, iron, and zinc, have significant consequences for human well-being and the socioeconomic development of communities around the world. An estimated two billion people suffer from micronutrient malnutrition and most of those affected are in developing countries. The Cassava Program of the Alliance of Bioversity International and CIAT is working on the development of yellow cassava (Manihot esculenta Crantz) genotypes that are high in carotenoid compounds as a strategy to reduce vitamin A deficiency. Cassava roots are very important for food security because they are a source of calories in the tropics, second only to rice, sugarcane, and maize crops. Cassava is mainly consumed cooked or fried. This cookbook offers alternative ways to prepare cassava, as a fresh root, cooked, and as flour through simple recipes that can be made at home. It encourages the use of cassava flour in bakery products as the main ingredient instead of wheat flour.